The urgent need to extend the appropriate use of ultrasound in Africa and worldwide. Overview, experiences and perspectives - Abbattista, Teresa; Meloni, Maria Franca; Ferraioli, Giovanna; Pirri, Clara (Frontiers in Public Health, 2024)
It is known that in African countries the health condition is problematic, both from a diagnostic and therapeutic point of view. Patients have to travel long distances to access medical care. Many cannot afford the cost of transportation to a medical facility. Ultrasound its into the scenario of healthcare imaging with limited resources, as an effective, economical, repeatable diagnostic tool, requiring low maintenance. Ultrasound tools in fact are relatively cheap and machines are easy to move, making them adapt to be taken to a rural setting where they are most needed. However ultrasound exams are not easy to perform and they need an adequate training. The spread of POCUS (point-of-care “focused” ultrasound) worldwide could be useful in Africa to identify high-risk patients. These cases selected in rural setting by POCUS can be referred to hospitals for further treatment. To deal with these situations it is necessary to form doctors and/or paramedical staff capable of guaranteeing a qualitatively adequate service. Therefore the need for basic training is greater in developing countries. Sharing successful educational strategies should advance the integration of ultrasound into the university medical school curricula. This will ensure that recently qualified doctors can practice their basic skills accurately and independently.